Light painting drawing application - Ng, Zhi Yun (2015)
Light painting is becoming a popular photographic technique nowadays. It is usually done in a dark environment when photographer control the light that is entering the camera lens during a long exposure shoot. This will create a “painted” image using the light on the photograph. There are infinite ways to light paint. Just a simple lighting tools such as flashlight, hand phone, or anything that emits light can create the light painting effect. The most traditional method for light painting is to draw using the light while taking a long exposure shoot. Long exposure shoot can easily be done by adjusting the shutter speed of the camera, or even using smart phone that provide various shooting option for the phone camera. Using this traditional method, photographer have to race against time in finishing his drawing before the shutter clicks. If the drawing is not as expected, photographer may have to redraw again. Hence, light painting can be a fun experience available to all ages and yet a tedious and tiring process. This project aims to develop a system that provide an alternative drawing method for the photographer. A drawing application would be developed in the project. Photographer can take the long exposure shoot by projecting the image that the photographer drew using the application. By taking photo while projecting the image on a glass panel in a dark environment would result in the light painting effect on the photograph. This would help the photographer skip all the tiring process of redrawing in order to obtain accuracy and precision of his painting.